Evil eye in the western Highlands - Maclagan, Robert Craig, 1839-1919 (Salt Lake City, UT : Project Gutenberg, 2023)
"Evil Eye in the Western Highlands" by Robert Craig Maclagan is a historical account written in the early 20th century. The work explores the prevalent superstition of the Evil Eye among the Gaelic-speaking populations of Scotland, diving into the origins, significance, and societal implications of this belief. It examines how the Evil Eye is viewed not just as a simple superstition, but as tied to deeper human emotions like envy and covetousness that challenge social harmony. The beginning of the text provides an introduction to the concept of the Evil Eye, framing it as a common superstition not limited to a specific region, but rather a universal aspect of human interaction. Maclagan discusses how feelings of hostility towards a neighbor, combined with fear of losing something valued, possibly originated the belief. He outlines how the Evil Eye manifests, linking it to social and moral dynamics within communities. Through various anecdotes and observations, the introduction lays the groundwork for further exploration of the belief that an envious glance can harm others, particularly livestock and children, often leading to a wide range of protective measures and rituals practiced by individuals in those societies. (This is an automatically generated summary.)
Release date is 2023-03-03
Susan Skinner, Les Galloway and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Folklore; Superstition; Evil eye